[PP.24.31] ONE YEAR SACUBITRIL/VALSARTAN THERAPY IS ASSOCIATED WITH DECREASE OF ARTERIAL STIFFNESS IN PATIENTS WITH STABLE HEART FAILURE WITH REDUCED EJECTION FRACTION. (September 2017) - Kobalava, Z.; Villevalde, S.; Lukina, O.; Babaeva, L.; Meray, I.
Abstract : Objective: Angiotensin receptor-neprilysin inhibitor (ARNI) is recommended to further reduce the morbidity and mortality for patients with chronic symptomatic heart failure with reduced ejection fraction (HFrEF). Increased arterial stiffness (AS) has been shown to correlate with adverse cardiovascular events. The aim of the study was to assess long-term sacubitril/valsartan effects on parameters of AS in patients with HFrEF. Design and method: In the open-label follow-up to PARADIGM HF study 16 patients with stable HFrEF (14 male, 69 ± 9 years (M ± SD), arterial hypertension 88%, previous myocardial infarction 88%, diabetes 43%, LVEF 32 ± 6%, eGFR 55 ± 13 ml/min/1.73 m 2, potassium 4.43 ± 0.38 mmol/l) were enrolled. Patients received a stable background treatment for at least a month (ACEI 94%, beta-blockers 100%, aldosterone receptor antagonists 81%, loop diuretics 75%). ACEI treatment was interrupted for 36 h and replaced with sacubitril/valsartan 50, 100 or 200 mg BID according to baseline BP (mean dose 185.7 ± 36.3 mg BID). AS was assessed by applanation tonometry baseline and after 6 and 12 months sacubitril/valsartan therapy. Wilcoxon and Spearman test was considered significant if p < 0.05. Results: After 6 months of sacubitril/valsartan therapy carotid-femoral pulse wave velocity (PWV) significantly decreased (11.5 ± 2.9 vs 10.2 ± 2.9 m/s, p < 0.05) while other parameters of AS did not change (p > 0.05). After 12 months sacubitril/valsartan therapy was associated with significant decrease of aortic augmentation pressure (AP) (15.3 ± 8.9 vs 10.5 ± 5.0 mmHg, p = 0.002), increase of reflected wave transit time (RWTT) (132 ± 9 vs 143 ± 29 ms, p = 0.02), subendocardial viability ratio (SEVR) (164 ± 25 vs 177 ± 37%, p = 0.009). Changes of PWV between 6 and 12 months were nonsignificant (10.2 ± 2.9 vs 10.8 ± 2.0 m/s; p > 0.05). Changes of augmentation pressure correlated with changes of SEVR (R = −0.56), augmentation index (AIx) (R = 0.52), stroke volume (R = 0.52), p < 0.05 for all. There was significant correlation between changes of SEVR and stroke volume (R = −0.85), changes of RWTT and AIx (R = −0.68), p < 0.05. Conclusions: In stable patients with HFrEF 12-month sacubitril/valsartan therapy is associated with significant improvement of central pulse wave parameters: decrease of aortic AP, increase of RWTT. Sacubitril/valsartan therapy was associated with beneficial increase of SEVR, index that reflects the subendocardial oxygen supply-demand ratio.